Strategies for Partitioning Narratives - Zhang, Zhen (SAGE open, 2024)
The Hollywood narrative film is often viewed as an overall causal relationship driven by the protagonist’s pursuits. Contrary to this point of view, this study treats the Hollywood narrative film as a complex of primary and secondary causal relationships dominated by protagonists and supporting roles, respectively, and proposes to use the protagonist-led causal relationship to segment the Hollywood narrative film. The paper also advocates the use of visual, verbal, and aural performance cues to demarcate primary and secondary narrative units. The narrative units obtained through this segmentation method can be used to study Hollywood narrative film development, characters, and the relation between narrative and performance. This paper selects four Hollywood films (Roman Holiday, Interstellar, Joker, and Lolita) representing different narrative paths to test the segmentation method. The validation process shows that the proposed method can effectively segment linear and non-linear Hollywood narrative films and distinguish narrative units. However, this study only applies the proposed segmentation method to limited Hollywood narrative films. Larger-scale validations are required in the future to test the effectiveness of the method and further refine it. Plain language summary This study examines how the protagonist-led causal relationship segments linear and non-linear Hollywood narrative films and how performative clues signify narrative unit boundaries. In order to achieve the research objectives, this study first proposes a Hollywood narrative film segmentation method, and then applies the method to small-scale Hollywood films with different running times and narrative techniques to test its effectiveness. The test result shows that the proffered method allows the segmentation of Hollywood narrative films with linear or non-linear sequences and the study of narrative techniques. The new method also contributes to the literature on the cognitive study of narratives by disclosing how the changes in visual, verbal, and aural performative clues form the boundaries between various primary and secondary narrative units. However, it should be admitted that this study has its limitations. The proposed segmentation method has only been tested on a small scale on linear and non-linear Hollywood narrative films. Future research needs to conduct large-scale tests on linear and non-linear Hollywood narrative films, especially non-linear films that unfold through various narrative techniques such as backstory, flashback, foreshadowing, and flash-forward.